Does Successful Aging Moderate the Link between Chronic Pain and Depressive Symptoms? - Naujalytė, Kamilė; Sargautytė, Rūta (Psichologija, 2025)
This study investigated whether the relationship between chronic pain and depression in older adults can be moderated by successful aging, based on the SOC theory (Baltes & Baltes, 1990). Its participants included 106 individuals aged 65 to 93 (M = 72.12, SD = 6.39), of whom, 89.6% were female and 10.4% male. Chronic pain was assessed by using the Pain Intensity, Enjoyment of Life and General Activity Scale (Krebs et al., 2009), depression was measured by using the Geriatric Depression Scale (Sheikh & Yesavage, 1986), and successful aging was assessed by using the Selection, Optimization, and Compensation Questionnaire (Freund & Baltes, 2002; Segura-Camacho et al., 2018). A cross-sectional correlational design was applied by using correlational and moderation regression analyses. The results showed a positive association between chronic pain and depression. Notably, the compensation strategy moderated this relationship: if using the compensation strategy less frequently, greater chronic pain predicted higher depression, while using compensation strategy more frequently the relationship between chronic pain and depression weakened. These findings highlight the role of compensation in moderating the association between depression and chronic pain in older adults. Despite its limitations, the study contributes to a deeper understanding of opportunities for improving psychological support for older adults experiencing chronic pain.